Amine-boranes reactions promoted by lanthanide(ii) ions. Issue 6 (22nd December 2021) - Kirkina, Vladislava A.; Kissel, Alexander A.; Selikhov, Alexander N.; Nelyubina, Yulia V.; Filippov, Oleg A.; Belkova, Natalia V.; Trifonov, Alexander A.; Shubina, Elena S.
Abstract : This study shows for the first time the catalytic activity in amine-borane dehydrogenation for lanthanide(ii ) species and unveils the step-by-step transformations of the starting complexes into active catalytic intermediates. Abstract : The catalytic activity in amine-borane dehydrogenation is shown for the first time for Ln(ii ) species using complexes [{( p-t Bu-C6 H4 )2 CH}2 M·L] (M = Yb, Sm, L = (DME)2, TMEDA). The protonation of M(ii )–C bonds with HNR 1 R 2 BH3 affords amidoborane complexes [M(NR 1 R 2 BH3 )2 L], which under excess HNMe2 BH3 transform to [NMe2 BH2 NMe2 BH3 ] − derivatives, both serving as the dehydrocoupling intermediates.